GAMBARAN GIZI SEIMBANG DI MASA PANDEMI PADA SISWA SMA NEGERI 4 MEDAN - Rahayu, Indah Tri; Tanjung, Ika Citra Dewi; Pasaribu, Ayodhia Pitaloka; Syarifah, Siti; Samosir, Fauzan Azmi Hasti Habibi (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2025)
Introduction: The Covid-19 pandemic has had a comprehensive impact, one of which is the availability of food which has an impact on family food preparation and nutritional needs. Nutritional problems in adolescents arise due to inadequate nutritional intake, namely an imbalance between nutritional intake and recommended nutritional adequacy. Nutritional problems that can occur in adolescents are underweight, obesity, and anemia. This study was conducted to determine the description of balanced nutrition knowledge during the pandemic in grade XI & XII students of SMAN 4 Medan. Method: This study is descriptive with a cross-sectional research design. The instrument used in the study was a questionnaire. The questionnaire was made by the researcher himself which was taken from related theories or references. The measuring instrument used in this study was a questionnaire using a google form. Results This study found that the level of knowledge about balanced nutrition during the pandemic in grade XI and XII students of SMA Negeri 4 Medan was in the good category of 194 people (73.5%), the sufficient category of 65 people (24.63%), and the lacking category of 5 people (1.89%). Discussion: Students of grade XI and XII of SMA Negeri 4 Medan have good knowledge about balanced nutrition during the pandemic, this is because students have obtained related theories from lessons at school and students' activeness in exploring related knowledge from the internet. Conclusion: Students of SMA Negeri 4 Medan have good knowledge about balanced nutrition during the pandemic.